(3GdJSjjQ GdYehej Hjf GdGJLGgGJ GdcdGSjcjI hGdGJLGgGJ GdMOjKIs - (3YOeGf(B, (3eQjRbs ((3GdLRGFQs (3GdLShQ ddfTQ h GdJhRjYs, 2018)
(3eaghe h CfhGY h eHGOF GdNOeI GdYehejI , GdEOGQI GdYehejI , eaghe h NUGFU h eHGOF GdGOGQI GdYehejI h GdHYO GdHjFj dgG h GdCWQGa PGJ GdeUdMI , , GdJSjjQ GdYehej eagheg h eOGNdg hhXGFag , Jbjje GdCOGA aj GdEOGQI GdYehejI , eONd dJfejI GdGOGQI GdYehej aj GdMhceI GdEdcJQhfjI , LhOI GdNOeGJ GdYehejI , CNdbjI GdEOGQI GdYehejI , GdJSjjQ GdYehej GdLOjO , eaghe heOGNd GdGUdGM GdEOGQj(B.s
Keywords: (3GdGOGQI GdYGeIs